(untitled) (Communications in Computational Physics, 2020)
This study is aimed at improving multiple adaptive subtraction. We propose a modified pseudomulti-channel matching method based on the Huber norm, to adjust the matching differences on frequency and phase between the predicted multiples and original data. The second-order derivative of the predicted multiples is utilized to replace the derivative of its Hilbert transform. Due to the additional frequency term, this method can enhance the high-frequency component. We introduce 180〫 phase rotation of the multiple channels, which can decrease phase differences. The Huber norm interpolates between smooth L2 norm treatment of small residuals and robust L1 norm treatment of large residuals. This method can eliminate the restriction of large value conditions from the L2 norm and weaken the condition of orthogonality from the L1 norm. The applications of the Pluto and Delft models shows that compared with pseudomulti-channel matching filter, the main frequency is increased from 36 Hz to 38 Hz, and the primary reflection wave is more concentrated. The practical application of field data verifies the effectiveness of the proposed method.